X-Band Multilayer Stacked Microstrip Antenna Using Novel Electromagnetic Band-Gap Structures. Issue 4 (19th May 2023) - Gaharwar, Mohit; Dhubkarya, D. C.
Abstract : In this work, a multi-layered rectangular microstrip antenna, with an inset feeding technique, is designed. It consists of a 10 GHz resonating conventional microstrip patch and a novel 9 × 9 electromagnetic bandgap (EBG) array printed on a 0.5 mm thin FR-4 epoxy as superstrate; an air-spacer separated both. The top radiating patch is magnetically coupled with the bottom radiator such that it also radiates. The bottom dielectric layer's other side is finished with the perfect ground for minimizing the back-lobe radiation. The dimensional parameters are optimized for both patch and the EBG surface in the Finite Element Method (FEM)-based EM solver ANSYS HFSS. The superimposition of the top EBG surface improves the gain without degrading the performance of the lower patch. This antenna has a −10 dB reflection bandwidth of 1.2 GHz with −30.57 dB minimum reflectivity at 9.9 GHz (better VSWR). The proposed prototype offers a gain of 9.45 dBi in both E and H planes. Finally, the device is fabricated using the conventional PCB technology. The performances of the device, like gain and radiation pattern, are measured in the anechoic chamber. It is found that the simulation and measured results are in near agreement. The physical dimensions of the proposed antenna are 55 mm × 55 mm × 17.67 mm.